Determine The Level Norms To Evaluate Physical Training Of The Volleyball Players - Amoura Yazid . (sports creativity, 2025)
This study aims to determine the standard normal distribution levels within the physical requirements to the equinoctial volleyball players,Starting from a basic base that the levels of all volleyball players fall within the good level where the quantitative values of the selected physical abilities are selected in order to extract the battery tests and put them within the framework of scientific and statistical,This study was also conducted in order to evaluate physical abilities according to the causal factors and the ratios of saturation coefficients and the prevalence of each physical characteris ticthere fore, the physical tests were determined by the battery of the extracted tests and then the real levels of the abilities level were determined. The study also found that physical abilities are determined according to a given order, which gives us the so-called determinants and in order to reach accurate results ,The most important results were that the overall level of physical capacity of all physical traits at the intermediate level, on the other hand, gave us the ability to assess physical preparation at certain standard levels